Development of Banana Milk Product Supplemented with Banana Peel Powder from Sub-standard Hom-Thong Banana (Musa acuminata) - Eakpetch, Patchaniya (Journal of Nutrition Association of Thailand (Online), 2024)
Bananas are classified as an economic crop in ASEAN. Currently, Thailand's Hom-Thong bananas are marketed both within the country and abroad due to the production of plants for export. Produce with good quality will be selected for export while that does not meet the standard for export is thrown away. When graded bananas are processed into products, there will be leftovers such as peels that are discarded as waste, which is a serious problem for farmers. Therefore, studying the economic utilization of bananas and banana waste, whether it is simple processing that farmers can do themselves or industrially to add value. It is another way to create careers and increase income for farmers. The objective of this research was to study the amount of sub-standard Hom-Thong banana peels in banana milk products. The ratio of banana pulp, milk powder, and water (grams per 100 grams) was studied using the experimental design program to design a set of experiments for Principal Component Analysis (PCA) with a multivariate technique for linear summation. Then, the best ingredient formula was used to develop a banana milk product fortified with banana peel powder at three levels: 0, 0.25, and 0.5 grams per 100 grams. The results of consumer acceptability using 9-points hedonic scale test by using 10 trained panelists showed that banana milk products with added banana peel powder equal to 0.5 grams per 100 grams (banana pulp, milk powder, water, and banana peel powder were 12.19, 29.35, 57.96, and 0.5 grams per 100 grams, respectively) had the overall acceptability score of 8 (like very much). While the experimental set with added banana peel powder of 0.25 grams per 100 grams (banana pulp, powdered milk, water, and banana peel powder were 12.22, 29.43, 58.1, and 0.25 grams per 100 grams, respectively) had moderate acceptability of color when compared to other experimental sets. The selected banana milk formula contained 0.5 grams of banana peel powder per 100 grams providing dietary fiber 0.75 grams per 1 serving (a box of 150 grams) which accounts for 0.8 percent of the recommended daily intake.